The Starmach Gallery in Kraków: The Gallery of Contemporary Art in a Former Jewish House of Prayer - Anna Jasińska; Artur Jasiński (Muzeológia a Kultúrne Dedičstvo, 2025)
The adaptation of the former Jewish Zucker House of Prayer as a gallery of contemporary art is a unique phenomenon due to both the complicated history of the heritage building itself and the unique personality of the current owner. Andrzej Starmach, an art dealer and collector in one, has gathered an extraordinary collection of contemporary Polish art, managing to stay ahead of popular trends. For many years, the Starmach Gallery was a lone beacon of culture in the run-down Podgórze district, which is now flourishing, becoming a location of numerous museums. Through their recent donation of their outstanding collection of Polish contemporary art – built up over a period of many years – to the city of Kraków, Andrzej and Teresa Starmach have left their mark on the history of Polish art collecting.